Motivational direction of professional socialization of students - O. Tapalova, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article discusses the motivational orientation of professional socialization of students. Motivational factors based on interest in the future profes- sion, the motives of self-actualization and teaching cognitive motives positively influence the professional socialization of modern students. The study re- sults show that only a high level of student motivation, form a high level of training of graduates and their high level of professional socialization.
Keywords: motivational orientation; higher education; professional socialization; motivational factors; students